A Cost-Effective Critical Path Approach for Service Priority Optimization in the Grid Computing Economy - LIN, Mei (Institutional Knowledge at Singapore Management University, 2004)
The advancement in the utilization and technologiesof the Internet has led to the rapid growth of gridcomputing; and the perpetuating demand for gridcomputing resources calls for an incentive-compatible solution to the imminent QoS problem. This paper examines the optimal service priority selection problem that a grid computing network user will confront. We model grid services for a multi-subtask request as a prioritized PERT graph and prove that the localized conditional critical path, which is based on the cost-minimizin gpriority selection for each node, sets the lower bound for the length of cost-effective critical path that commits the optimal solution. We also propose a heuristic algorithm for relaxing the nodes on the non-criticalpaths with respect to a given critical path.